Strategies of Creating the Inventor’s Image in Popular Science Discourse - O. V. Ramantova; N. V. Stepanova (Дискурс)
Introduction. The present paper aims at revealing and describing the linguistic means of creating the inventor’s image in the English language science popular discourse. The study also describes the use of image creation strategy and solidarity strategy. The relevance of the research is defined, firstly, by unconditional and ever-increasing public interest in scientific knowledge in the era of technological progress. Secondly, regarding the obvious importance of the human factor in the presentation of an invention from the creator’s point of view makes it possible for the mass reader to interpret the science news in various ways and see the modern inventor’s most typical features. Thus, analyzing the specific representation of the invention in popular science media texts the authors offer their own original conception of a modern innovator, which defines the novelty of the study. Special attention is focused on credibility and competitive nature of science popular discourse which are its integrative features.Methodology and sources. The research is based on the English language sciencepopular media texts – Popular Mechanics, Mit News Education, Science Daily, Interesting Engineering, SciTechDaily. For the selection of technically-focused media texts the continuously sampling method was used. The general methodology of studying image creation strategy and solidarity strategy also includes the method of semantic analysis, the method of semantic-stylistic analysis, elements of communicative-pragmatic analysis and the method of contextual analysis.Results and discussion. Image creation strategy and solidarity strategy are implemented in science popular discourse mainly on lexical and syntactic levels and imply the use of stylistic devices. Each of the strategies mentioned above matches a certain type of science popularized texts about inventions and discoveries. The first type is about the selfpresentation of the innovator, and has its own linguistic features. The second type includes the description of an invention from the position of scientific community. The significant result of the study is the conclusion about the diverse nature of the inventor’s media image.Conclusion. The study of the linguistic specific of the inventor’s image allows a deeper understanding of the anthropocentric nature of an invention itself. The last one is inseparable from its creator being the result of scientific activity and professional ambitions, as well as the personal growth condition. The chosen methodology can be applied for further research and to similar studies of the creator and his creation based on texts of different profile.